2020
DOI: 10.1080/14756366.2020.1722120
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, anti-inflammatory, cytotoxic, and COX-1/2 inhibitory activities of cyclic imides bearing 3-benzenesulfonamide, oxime, and β-phenylalanine scaffolds: a molecular docking study

Abstract: Cyclic imides containing 3-benzenesulfonamide, oxime, and b-phenylalanine derivatives were synthesised and evaluated to elucidate their in vivo anti-inflammatory and ulcerogenic activity and in vitro cytotoxic effects. Most active anti-inflammatory agents were subjected to in vitro COX-1/2 inhibition assay. 3-Benzenesulfonamides (2-4, and 9), oximes (11-13), and b-phenylalanine derivative (18) showed potential anti-inflammatory activities with 71.2-82.9% oedema inhibition relative to celecoxib and diclofenac (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The imide core is also present in compounds whose activity is related to CNS activity [ 32 , 33 , 34 , 35 , 36 ]. In particular, much attention has been paid to their ability to inhibit cyclooxygenases, anti-inflammatory, and analgetic activity [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. To date, several drugs with cyclic imide structure have been approved, including lurasidone, buspirone, ethosuximide, mesuximide, and the IMiDs class includes thalidomide and its analogues lenalidomide, pomalidomide, apremilast ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The imide core is also present in compounds whose activity is related to CNS activity [ 32 , 33 , 34 , 35 , 36 ]. In particular, much attention has been paid to their ability to inhibit cyclooxygenases, anti-inflammatory, and analgetic activity [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. To date, several drugs with cyclic imide structure have been approved, including lurasidone, buspirone, ethosuximide, mesuximide, and the IMiDs class includes thalidomide and its analogues lenalidomide, pomalidomide, apremilast ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effect of 12r on iNOS and COX‐2 expression was confirmed (Figure 5f). Moreover, there was no apparent inhibition of COX‐1 expression (Abdel‐Aziz et al., 2020). Overall, these results indicated that compound 12r exerted an inhibitory effect on the activation of NF‐κB and related pro‐inflammatory mediators.…”
Section: Resultsmentioning
confidence: 99%
“…Two chemical entities appear with weighing importance in the OPLS-DA model, 2-Methylpropanoyl phosphate and 1,3-Benzenedisulfonamide; however, neither of them has been previously reported in the human metabolome. Interestingly, compounds containing the sulphonamide moiety present potential biological activities, such as carbonic anhydrase and COX-1/2 inhibition, as well as anti-inflammatory, and antitumor activities [ 47 ].…”
Section: Discussionmentioning
confidence: 99%